Proportionality in Mandatory Green Building Certification: A Legal-Economic Analysis - ., Sutikno; Wibowo, M. Agung; Soeharto, Achmad (Dinasti Research, 2025)
The Mandatory green building certification has emerged as a central policy tool to advance sustainable development and reduce the environmental impacts of the construction sector, yet in Indonesia, it operates within a hybrid regulatory framework that combines statutory rules with non-state technical standards. This study examines whether such mandatory certification is legally sound, economically rational, and proportionate in relation to the burdens it imposes on regulated actors. Using a juridical–economic approach, the research integrates doctrinal legal analysis with public policy economics by examining national statutes, ministerial and regional regulations, and private certification standards, alongside academic literature and international policy reports. The analysis is conducted qualitatively through legal interpretation, cost–benefit reasoning, and a proportionality test based on the criteria of legitimate aim, suitability, necessity, and proportionality stricto sensu. The findings show that mandatory green building certification clearly pursues a legitimate public objective, environmental protection and sustainable development, but its implementation raises concerns about legal certainty and distributive justice. Reliance on non-state standards without explicit statutory delegation creates normative ambiguity, while significant upfront compliance costs for design, technology, and certification disproportionately affect small and medium-sized enterprises. As a result, the policy satisfies the requirement of a legitimate aim but does not fully meet the elements of necessity and proportionality in the strict sense, since it is not always the least restrictive or most balanced means of achieving environmental goals. The study’s novelty lies in its integrated legal–economic assessment of green building certification through the principle of proportionality, offering a holistic framework that evaluates environmental regulation not only as a matter of legal validity but also as an instrument of economic rationality and fair burden-sharing in public policy.